Reduction of morbidity in hepatosplenic Schistosomiasis mansoni after treatment with praziquantel: a long term study - Ana Lúcia C. Domingues; Amaury D. Coutinho (Revista da Sociedade Brasileira de Medicina Tropical, 1990)
Forty-two with hepatosplenic patients treated with praziquantel and followed up for 5 years. One half of the patients received a single 30 mg/kg dose and the other half, two doses of 25 mg/kg given 4 hrs apart. According to Hoffman and Kato-Katz stool exams, an 83.3% cure rate, was observed after twelve months. Stool egg counts in cases of incomplete cure were greatly reduced. Liver function, as assessed by serum levels of aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase and alkaline phosphatase activities as well as albumin and gamma globulin showed marked improvement after one year. Hepatomegaly was reduced in 81.0% of patients and splenomegaly in 78.8%. Spleen regression was complete in 15.1% of the total, and in 18.5% of those with compensated hepatosplenic disease. As a result of these observations, the authors recomend early treatment with anti-schistosomal medication, either oxamniquine or praziquantel, to halt progression of disease and reduce splenomegaly.